(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
My research paper is called Darbari Jhumur. Jhumur is a folk song of South West Frontier Bengal. A part of jhumor is Darbari jhumur. I claim that Barjuram Das is the creator of this jhumur. Darbari jhumors were sung by various royal families. Various genres are created around this Jhumur. The land of Darbari jhumur was once spread abroad. In the later period, the Darbari jhumur gradually disappeared. At present several courtly jhumors can be heard in the jhumur arena.